2013
DOI: 10.1371/journal.pone.0078105
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial RNA Landscape of Saccharomyces cerevisiae

Abstract: Mitochondria are essential organelles that harbor a reduced genome, and expression of that genome requires regulated metabolism of its transcriptome by nuclear-encoded proteins. Despite extensive investigation, a comprehensive map of the yeast mitochondrial transcriptome has not been developed and all of the RNA-metabolizing proteins have not been identified, both of which are prerequisites to elucidating the basic RNA biology of mitochondria. Here, we present a mitochondrial transcriptome map of the yeast S28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
121
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 110 publications
12
121
1
Order By: Relevance
“…Of hybrids associated with ORFs, 42% occurred in the 10% most highly expressed genes. Hybrids also occurred in the polymerase II-driven sn/snoRNAs, ncRNAs, and Ty1 elements; polymerase I-driven rDNA; polymerase III-driven tRNA and other genes; and, as previously noted by El Hage et al (2014), the mitochondrial genome-all of which are highly expressed (Curcio et al 1990;French et al 2003;Pelechano et al 2010;Turk et al 2013;Jordán-Pla et al 2015). High expression alone is sufficient for R-loop formation regardless of genomic context, as both the transposition of highly expressed genes to an artificial chromosome and overexpression of low transcribed ORFs caused R loops.…”
Section: Discussionsupporting
confidence: 72%
“…Of hybrids associated with ORFs, 42% occurred in the 10% most highly expressed genes. Hybrids also occurred in the polymerase II-driven sn/snoRNAs, ncRNAs, and Ty1 elements; polymerase I-driven rDNA; polymerase III-driven tRNA and other genes; and, as previously noted by El Hage et al (2014), the mitochondrial genome-all of which are highly expressed (Curcio et al 1990;French et al 2003;Pelechano et al 2010;Turk et al 2013;Jordán-Pla et al 2015). High expression alone is sufficient for R-loop formation regardless of genomic context, as both the transposition of highly expressed genes to an artificial chromosome and overexpression of low transcribed ORFs caused R loops.…”
Section: Discussionsupporting
confidence: 72%
“…This correlation is consistent with NAD + being added to 5′ ends cotranscriptionally. Moreover, transcription initiation in mitochondria begins with an adenosine residue at all promoters (20). Surprisingly, we saw no enrichment of the COX1 mRNA, which is at the 5′ end of a transcription unit in the mitochondrial genome and is not known to undergo 5′ end processing (20).…”
Section: Significancementioning
confidence: 64%
“…Moreover, transcription initiation in mitochondria begins with an adenosine residue at all promoters (20). Surprisingly, we saw no enrichment of the COX1 mRNA, which is at the 5′ end of a transcription unit in the mitochondrial genome and is not known to undergo 5′ end processing (20). However, closer inspection of the RNA-Seq reads for COX1 revealed that the reads do not extend to the transcriptional start site (Fig.…”
Section: Significancementioning
confidence: 80%
See 1 more Smart Citation
“…This suggests that the two proteins are functional analogs. The fact that the deficiency in human elongation factor results in a more severe phenotype than inactivation of Mss116p in yeast may be due to the organization of the human mt genome, which has just two promoters from which much longer transcripts are synthesized, whereas in yeast mitochondrial transcription involves multiple promoters driving transcription over much shorter regions (68). On the other hand, yeast are exposed to more severe environmental stress than the cells of multicellular organisms, making the presence of an analogous elongation factor that would stabilize transcription complexes essential under certain stress conditions but perhaps not under all conditions.…”
Section: Discussionmentioning
confidence: 99%